2018
DOI: 10.1016/j.ajo.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Controlled, Phase 2 Trial of Povidone-Iodine/Dexamethasone Ophthalmic Suspension for Treatment of Adenoviral Conjunctivitis

Abstract: PVP-I/dexamethasone appeared safe and well tolerated, and significantly improved clinical resolution and adenoviral eradication in patients with acute adenoviral conjunctivitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 28 publications
1
18
0
2
Order By: Relevance
“…More recently, Pepose et al. () have shown that PVP‐I 0.6%/dexamethasone 0.1% appeared safe and well tolerated and significantly improved clinical resolution and adenoviral eradication in patients with acute adenoviral conjunctivitis. Furthermore, Musumeci et al.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Pepose et al. () have shown that PVP‐I 0.6%/dexamethasone 0.1% appeared safe and well tolerated and significantly improved clinical resolution and adenoviral eradication in patients with acute adenoviral conjunctivitis. Furthermore, Musumeci et al.…”
Section: Introductionmentioning
confidence: 99%
“…1 An ophthalmic suspension composed of PVP-I 0.6% and the corticosteroid dexamethasone 0.1% (PVP-I 0.6%/DEX 0.1%) has been evaluated in a Phase 2 trial. 26 Results from this study showed that PVP-I 0.6%/DEX 0.1% treatment of patients with acute adenoviral conjunctivitis significantly improved clinical resolution and eradication of adenovirus in the study eye. 26 Another compound, N-chlorotaurine, has broad-spectrum microbicidal activity due to its nonspecific reaction mechanism, and was investigated for the treatment of viral conjunctivitis.…”
Section: Viral Conjunctivitismentioning
confidence: 68%
“…26 Results from this study showed that PVP-I 0.6%/DEX 0.1% treatment of patients with acute adenoviral conjunctivitis significantly improved clinical resolution and eradication of adenovirus in the study eye. 26 Another compound, N-chlorotaurine, has broad-spectrum microbicidal activity due to its nonspecific reaction mechanism, and was investigated for the treatment of viral conjunctivitis. 27 A 1% solution of N-chlorotaurine was well tolerated in patients with EKC and shortened the course of disease compared with gentamicin eye drops in a randomized phase 2b study.…”
Section: Viral Conjunctivitismentioning
confidence: 68%
See 1 more Smart Citation
“…Few well-designed studies have established the efficacy of Betadine eye drops in viral conjunctivitis. [ 5 ] For a case of conjunctivitis with COVID-19, this preparation may help to reduce the viral load due to its action against a wide range of viruses. Burning and irritation is a significant side effect of the drug, which can be effectively reduced by diluting 1 mL of 5% Betadine with 4 mL of BAK containing lubricant drops.…”
mentioning
confidence: 99%